Factors Affecting the Selection of the Procurement Methods for Construction Projects in Malaysia - Yap, Zhi Shan; Kong, Sio Kah; Lee, Hai Chim, Benny (INTI International University, 2019)
The selection of an appropriate procurement method is becoming an increasingly important issue due to complex decision-makings by clients early of project lifecycles. The aim of this research is to improve and enhance procurement system in Malaysia’s construction industry through identifying, evaluating and ranking essential factors that affect the selection of the traditional and the non-traditional procurement methods from consultant quantity surveyors’ perspectives. An extensive literature review of various procurement methods and factors which influence the selection of an appropriate procurement method for construction projects in Malaysia was conducted. A survey by questionnaire was carried out to elicit professionals' views on factors that influence the selection of procurement method for their planned projects; a total of 31 consultant quantity surveyors responded the survey. The data was then analysed using frequency analysis which then displayed in pie chart form and the factors were ranked according to their Relative Importance Index (RII). The results indicate that the top three significant factors that have most influence on the selection of procurement methods in Malaysia’s construction projects are: price certainty; degree of project complexity; time constraints of project. This research concludes that there is lack of variety of procurement methods used in the Malaysia’s construction industry where traditional procurement methods are preferred. This is because majority of professionals in Malaysia are not familiar and not widely experienced with the other alternative procurement methods. It is therefore highly recommended that the parties involved in the selection process should consider carefully all the available procurement methods for works which include study them and analyse their pros and cons to know their effects on the projects. Lastly, the project performance criteria must be established and match against the performance outcomes of the various methods before selecting.